2004
DOI: 10.1111/j.0041-1132.2004.04156.x
|View full text |Cite
|
Sign up to set email alerts
|

The hepatitis C virus genotype and subtype frequency in hepatitis C virus RNA‐positive, hepatitis C virus antibody‐negative blood donors identified in the nucleic acid test screening program in Poland

Abstract: The frequency of wp donors is 18.5 per 1 million. The unexpected high frequency of Genotype 4 and Subtype 3a and the low frequency of Subtype 1b was observed in wp donors compared to anti-HCV-positive individuals. Additional epidemiologic questioning introduced after HCV RNA detection may help to identify infection source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
0
18
1
2
Order By: Relevance
“…A Siberian study reported that the risk factor for HCV infection was higher among patients who had at least four sexual partners during their lives history, homosexual behaviour, or a history of STD (35). All other potential risk factors reported by the patients (HCV RNA-positive heterosexual partner, two or more heterosexual partners, dental procedures, body piercing and tattooing) also appeared in a study carried out by Brojer et al (7) and Orton et al (30). The results confirm the advantage of interviewing rather than patients completing a routine questionnaire to identify risk factors.…”
Section: Discussionmentioning
confidence: 85%
“…A Siberian study reported that the risk factor for HCV infection was higher among patients who had at least four sexual partners during their lives history, homosexual behaviour, or a history of STD (35). All other potential risk factors reported by the patients (HCV RNA-positive heterosexual partner, two or more heterosexual partners, dental procedures, body piercing and tattooing) also appeared in a study carried out by Brojer et al (7) and Orton et al (30). The results confirm the advantage of interviewing rather than patients completing a routine questionnaire to identify risk factors.…”
Section: Discussionmentioning
confidence: 85%
“…However, other studies of pediatric populations in different parts of Poland did not confirm those findings [Wysocki et al, 1994;Woźniakowska-Gęsicka et al, 1997]. Interestingly, HCV genotype 4 was found in as many as 14% of 50 window-period (anti-HCV negative and HCV-RNA-positive) blood donors identified in a nucleic acid test screening program in Poland, compared to 1.4% with genotype 4 in the control group of anti-HCV seropositive blood donors [Brojer et al, 2004]. The differences in genotype distribution between the two groups could be attributed to the relative increase in frequency of genotype 4 in recently acquired (windowperiod) infections.…”
Section: Discussionmentioning
confidence: 94%
“…Among 70 anti‐HCV‐positive blood donors, 75.7% were genotype 1b, 4.3% genotype 1a, 14.3% genotype 3a, 4.3% genotype 4 and 1.4% genotype 6. Among 170 hepatitis patients, 85.3% were genotype 1b, 0.6% genotype 1a, 10.6% genotype 3a, 1.2% genotype 4 and 2.4% mixed (241).…”
Section: Resultsmentioning
confidence: 99%